Web-Based Network Device Monitoring Tool Using Simple Network Management Protocol (Snmp) - Hossen, Md.Jakir (2003)
The Internet enables different computer networks to join together into one network in which many different models of network devices can co-exist with each other. Standard management protocol is necessary for the purpose of managing these networks. SNMP (Simple Network Management Protocol), one of the standard protocols, is designed for this open-class management function and is successfully implemented. This thesis suggests a monitoring of network device statistical data from a remote place. This approach reduced the complexity of existing techniques, which are basically operable in specific operating system and having no standard Graphical User Interface (GUI). To address this problem, a system based on WWW standard tool is developed which is SNMP compatible as well as operable with any network device. The network device monitoring tool is a client program, which is managed and could be contacted with the server program. A web server and a browser are to provide static, dynamic, and interactive management information. A web server, which plays a managing role, offers a variety of types of information. An SNMP agent, which cooperates with a web server, uses SNMP protocol and provides access to management information of network devices/agents. The implementation of the user interface using the web-based technique of Java Applet makes it possible for a manager to easily search and manage agent Management Information Base (Mill) through a browser. Java SNMP class files and SNMP Applet Server (SAS) classes are used inside the Web-server to communicate with network devices. The network device monitoring tool is configured to collect network statistical data. It can monitor the real time graph on the basis of MIB variable from remote place and shows more efficient than the existing tool.